Raloxifene for older women: a review of the literature - Helga Hansdóttir (Dove Medical Press, 2008)
Helga HansdóttirDepartment of Geriatrics, Landspitali University Hospital, Landakoti, Reykjavik, IcelandAbstract: Raloxifene is a non-steroidal selective estrogen-receptor modulator (SERM) which is used for prevention and treatment of postmenopausal osteoporosis. Raloxifene decreases the incidence of vertebral fractures by 30%–50% in postmenopausal women with osteoporosis but has not been shown to decrease the incidence of hip fractures or other non-vertebral fractures. At the present time, estrogen-replacement therapy and bisphosphonate treatment are the only medical treatments that are proven to prevent hip fractures with the exception of vitamin D and calcium replacement, which has been shown to prevent hip fractures in elderly individuals and nursing home residents. Raloxifene has been shown to have additive effects on bone turnover and bone mineral density (BMD) when used along with alendronate and teriparatide. Raloxifene could have a role in renal failure as it has been shown to increase BMD of the vertebra over 1 year of therapy. Raloxifene is as effective as tamoxifen in reducing the risk of invasive breast cancer. The increased incidence of venous thromboembolism is the main concern of raloxifene therapy and previous history of venous thromboembolism is a contraindication for use of raloxifene. Raloxifene has a role in treatment of vertebral osteoporosis in older women. The decision to use raloxifene should be based on evaluation of fracture risk and on potential other benefits than fracture reduction along with consideration of side effects.Keywords: SERM, raloxifene, osteoporosis, women, fractures, old age